Phosphine on Jupiter and Saturn from Cassini/CIRS - Fletcher, L; Orton, G; Teanby, N; Irwin, P (2009)
The global distribution of phosphine (PH3) on Jupiter and Saturn is derived using 2.5 cm-1 spectral resolution Cassini/CIRS observations. We extend the preliminary PH3 analyses on the gas giants [Irwin, P.G.J., and 6 colleagues, 2004. Icarus 172, 37-49; Fletcher, L.N., and 9 colleagues, 2007a. Icarus 188, 72-88] by (a) incorporating a wider range of Cassini/CIRS datasets and by considering a broader spectral range; (b) direct incorporation of thermal infrared opacities due to tropospheric aerosols and (c) using a common retrieval algorithm and spectroscopic line database to allow direct comparison between these two gas giants. The results suggest striking similarities between the tropospheric dynamics in the 100-1000 mbar regions of the giant planets: both demonstrate enhanced PH3 at the equator, depletion over neighbouring equatorial belts and mid-latitude belt/zone structures. Saturn's polar PH3 shows depletion within the hot cyclonic polar vortices. Jovian aerosol distributions are consistent with previous independent studies, and on Saturn we demonstrate that CIRS spectra are most consistent with a haze in the 100-400 mbar range with a mean optical depth of 0.1 at 10 μm. Unlike Jupiter, Saturn's tropospheric haze shows a hemispherical asymmetry, being more opaque in the southern summer hemisphere than in the north. Thermal-IR haze opacity is not enhanced at Saturn's equator as it is on Jupiter. Small-scale perturbations to the mean PH3 abundance are discussed both in terms of a model of meridional overturning and parameterisation as eddy mixing. The large-scale structure of the PH3 distributions is likely to be related to changes in the photochemical lifetimes and the shielding due to aerosol opacities. On Saturn, the enhanced summer opacity results in shielding and extended photochemical lifetimes for PH3, permitting elevated PH3 levels over Saturn's summer hemisphere. © 2009 Elsevier Inc.